Technology and the pursuit of economic growth / by David C. Mowery and Nathan Rosenberg - Mowery, David C.; Rosenberg, Nathan (Cambridge, 1989)
Technology's contribution to economic growth and competitiveness has been the subject of vigorous debate in recent years. This book demonstrates the importance of a historical perspective in understanding the role of technological innovation in the economy. The authors examine key episodes and institutions in the development of the U.S. research system and in the development of the research systems of other industrial economies. They argue that the large potential contributions of economics to the understanding of technology and economic growth have been constrained by the narrow theoretical framework employed within neoclassical economies. A richer framework, they believe, will support a more fruitful dialogue among economists, policymakers, and managers on the organization of public and private institutions for innovation. David Mowery is Associate Professor of Business and Public Policy at the School of Business Administration, University of California, Berkeley. Nathan S. Rosenberg is Fairleigh Dickinson Professor of Economics at Stanford University. He is the author of Inside the Black Box: Technology and Economics (CUP, 1983).
Keywords: Technology